High Power Self-Q-Switching in Nd:LuAG Laser - Guangju Zhang; Xing Fu; Yijie Shen; Mali Gong (IEEE Photonics Journal, 2018)
A compact pulsed Nd:LuAG laser at 1064 nm based on the self-Q-switching technique is reported, having the output power as high as 6.61 W at the incident pump power of 21.32 W, corresponding to the optical conversion efficiency of ∼31%. The temporal width of the pulse was in the range from 532.2 to 652.6 ns, and the repetition rate varied between 488.6 and 551.9 kHz. To the best of our knowledge, this is the first report on the self-Q-switching Nd:LuAG laser. With the nonlinear refractive index calculated to be 1.8 × 10–19 m2/W, and the numerical simulation made with the modified rate equations, the Kerr lens effect was believed to be the reason for the self-Q-switching of Nd:LuAG. The compact cavity generating pulses with high output power and high repetition rate not only reveal that the self-Q-switching technique could be an efficient method for the generation of pulses with high output power and high repetition rate, but enrich the characteristics of Nd:LuAG crystal.